Peran Analisis Neraca Air untuk Perencanaan Pertanian di Kabupaten Konawe Selatan - fathnur, Fathnur; Kunta, Thamrin; Musyadik, Musyadik (Indonesian Center for Agriculture Land Resource Development, 2021)
Abstract. Water is a natural resource that has various functions for both potable water and economic activities such as industry, agriculture and tourism. The availability of groundwater, which mostly comes from rainfall, is an important limiting factor for increasing plant production. The concept of the environmental hydrological cycle (for example in a watershed) states that the amount of water somewhere on the earth surface is influenced by the amount of water that enters / absorbs (input) and leaves (output) at a certain time. The balance of water input and output at a certain area is known as water balance. Water balance is a method that can be used to see the availability of groundwater for plant at a certain time. One of the procedures for calculating the water balance is based on the Thornthwaite and Mather (1957) method. Water balance calculation needs to be done in every agricultural planning in line with climate change. The purpose of this paper is to examine the use of a general water balance for agricultural planning in Konawe Selatan District, Southeast Sulawesi Province. Abstrak. Air merupakan sumberdaya alam yang memiliki beragam fungsi baik sebagai konsumsi air bersih maupun kegiatan perekonomian seperti industri, pertanian, dan pariwisata. Ketersediaan air tanah yang sebagian besar berasal dari curah hujan merupakan factor pembatas yang penting bagi peningkatan produksi suatu tanaman. Konsep siklus hidrologi lingkungan menyatakan bahwa jumlah air disuatu luasan tertentu di permukaan bumi dipengaruhi oleh besarnya air yang masuk/meresap (input) dan keluar (output) pada jangka waktut ertentu. Neraca masukan dan keluaran air disuatu tempat dikenal sebagai neraca air (waterbalance). Neraca air merupakan suatu metode yang dapat digunakan untuk melihat ketersediaan air tanah bagi tanaman pada waktut ertentu. Salah satu prosedur perhitungan neraca air adalah berdasarkan metode Thorntwaite dan Mather (1957) dengan satuan tinggi air (mm). Tujuan dari penulisan makalah ini adalah menelaah penggunaan neraca air umum untuk perencanaan pertanian berdasarkan hasilpenelitian di Kecamatan Lamooso Kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara.